Existence of Solutions for Fractional Boundary Value Problem with Nonlinear Derivative Dependence - Wenzhe Xie; Jing Xiao; Zhiguo Luo (Abstract and Applied Analysis)
We investigate the existence of solutions for fractional boundary value problem including both left and right fractional derivatives by using variational methods and iterative technique.